Review on fused deposition modelling extruder types with their specialities in filament extrusion process - Md Azhar, Muhammad Afif; Sukindar, Nor Aiman; Ani, Mohd Hanafi; Anuar, Hazleen; Kamaruddin, Shafie; Syed Shaharuddin, Sharifah Imihezri; Mustafa, Mohd Yusry; Adesta, Erry Yulian Triblas; Arief, Rudi Kurniawan; Sulaiman, Mohd Hafis (Springer, 2023)
3D printing is one of the growing technologies in the entry era of the industrial revolution 4.0. Fused Deposition Modelling (FDM), one of the 3D printing methods, has advantages in the manufacturing process where various product shapes can be made. One of the advantages of FDM lies in the extruder used. Various types of extruders can be used and installed on FDM machines. Findings from a review of five types of extruders found that some models have the ability to extrude specific types of material. Each extruder has advantages and specializations, which can affect the printing result. Therefore, this paper reviews the types of extruders for FDM and their capabilities so that the selection of the type of extruder to be used can be made accurately.